1975
DOI: 10.1007/bf00735742
|View full text |Cite
|
Sign up to set email alerts
|

Uneinheitlicher Phänotyp bei Partialtrisomie 4q

Abstract: The clinical and cytogenetic data of 3 non-related patients who have a partial trisomy 4q in common are reported. The chromosome aberration originated from a parental balanced translocation in 2 cases (t(3p+;4q--)and t(4q--;18q+)); in the 3rd case an inverted insertion of 4q22 yields q34 into 4q34 occured spontaneously. A comparison of the symptoms exhibited by these probands and 7 cases from the literature gives no indication of an uniform phaenotype of this aberration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 9 publications
1
28
1
Order By: Relevance
“…To our knowledge, 17 studies have described the pure 4q duplication region covering the 4q22q32 region [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] 30,31 Contrary to the reports of these researchers, we did not observe thumb or renal abnormalities in our patients having a 4q22q32 duplication. To our knowledge, the present study is the first report of a pure and recurrent 4q duplication investigated with CGH microarray technology and microsatellite analysis.…”
Section: Discussioncontrasting
confidence: 96%
“…To our knowledge, 17 studies have described the pure 4q duplication region covering the 4q22q32 region [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] 30,31 Contrary to the reports of these researchers, we did not observe thumb or renal abnormalities in our patients having a 4q22q32 duplication. To our knowledge, the present study is the first report of a pure and recurrent 4q duplication investigated with CGH microarray technology and microsatellite analysis.…”
Section: Discussioncontrasting
confidence: 96%
“…Thus our patient is the second case with the same partial trisomy and the first description of pure duplication without associated monosomy 1,2 . Comparison of the clinical manifestations in our patient and cases with pure duplication of 4q reported previously 7,[11][12][13][14][15] is summarized in Table 1. Our patient demonstrates majority of clinical features according to the criteria established by Halal et al 7 and Jeziorowska et al 15 .…”
Section: Discussionmentioning
confidence: 97%
“…Most of these have resulted from an unbalanced segregation of a familial translocation [Schrott et al, 1974;Biederman and Bowen, 1976;Cervenka et al, 1976;Yunis et al, 1977;Andrle et al, 1979;Mattei et al, 1979;Stella et al, 1979;Fryns and Van den Berghe, 1980;Merlob et al, 1989;Nucci et al, 1990;Petit et al, 1991;Fryns et al, 1993;Duval et al, 1994;Chen et al, 1997]. These direct duplications are more reliable in deriving accurate genotype-phenotype correlation [Dutrillaux et al, 1975;Vogel et al, 1975;Taylor et al, 1977;Fryns and Van den Berghe 1980;Halal et al, 1991;Jeziorowska et al, 1993;Goodman et al, 1997;Zollino et al, 1995;Navarro et al, 1996;Muraki et al, 1997]. Pescia et al [1982] reported on a patient with mental retardation and minor anomalies with one cell line with a deletion of chromosome 4q12→q13 and a second cell line with insertion of the same segment into one chromosome 4, resulting in partial monosomy/ trisomy of chromosome 4q.…”
Section: Discussionmentioning
confidence: 99%